Deafening - Itani, Frances, 1942-. (Canada : HarperPerennial, 2004)
Elegantly written and profoundly moving, Frances Itani's debut novel, Deafening, is a tale of virtuosity and power, set on the eve of the Great War and spanning two continents and the life of a young deaf woman in Canada named Grania O'Neill. d.
Keywords: World War, 1914-1918 -- Fiction; Dünya Savaşı, 1914-1918 -- Roman; Deaf women -- Fiction; Sağır kadınlar -- Roman; Ontario -- Fiction; Ontario -- Roman